The cultural contradictions of democracy : political thought since September 11 - Brenkman, John (Princeton University Press, 2007)
Since 9/11, American foreign policy has been guided by grand ideas like tyranny, democracy, and freedom. And yet the course of events has played havoc with the cherished assumptions of hawks and doves alike. The geo-civil war afflicting the Muslim world from Lebanon through Iraq and Afghanistan to Pakistan confronts the West with the need to articulate anew what its political ideas and ideals actually are.